PERANCANGAN PLTS TERAPUNG DI BENDUNGAN SIDAN KABUPATEN BADUNG - Paisal, Muhammad; Setiawan, I Nyoman; Satya Kumara, I Nyoman; Dwi Girantari, Ida Ayu; Sukerayasa, I Wayan; Indra Partha, Cok Gede (Jurnal SPEKTRUM, 2024)
Potential of renewable energy is essential to support Bali Clean Energy, one of the energy that can be exploited is Solar energy. However, by 2023 the potential has been exploited only 1,48 percent. One of the reasons why Solar Plant construction in Bali is slow is because it is difficult to find land large enough to build Solar Plant on a large scale. However, solution to overcome land constraint is to utilize the water body through floating Solar Plant application. In the Project, the Floating Solar Plant Sidan Dam utilized body of the Water Dam and work pictures from the Planing of the Sidan Dam, with such data being used to determine the Floating solar Plant System in Sidan Dam. The design results showed that floating Solar Plant in Sidan Dam has a potential capacity of 1.45 MWp with a total of 2640 units solar panel and uses 12 units of inverters of 1.100 kW capacity. The energy production produced by the floating Solar Plant in a year was 2.564.007 kWh.